Effects of GS-CA1 on nuclear envelope-associated early HIV-1 infection steps - Amita Singh; Victor Fourcassié; Victor Fourcassié; Karen Cristine Gonçalves Dos Santos; Hocine Chelbi; Natacha Merindol; Arnaud Droit; Arnaud Droit; Hugo Germain; Lionel Berthoux (Frontiers in Virology)
The novel HIV-1 drugs GS-CA1 and the recently approved lenacapavir (GS-6207) target the viral structural protein capsid (CA). However, their multiple mechanisms of action have not been fully characterized. Here, we investigated the effects of GS-CA1 on the early stages of HIV-1 infection, specifically the steps involving the nuclear envelope, in comparison to the antiviral cytokine IFN-β. Mass spectrometry data indicated that nuclear envelope proteins were only modestly affected by either GS-CA1 treatment or HIV-1 infection, but combining the two had a more significant impact, altering the levels of many proteins including proteasomal components. GS-CA1 induced a small but clear accumulation of HIV-1 capsid cores at nuclear pores, as seen by microscopy, whereas IFN-β caused a strong accumulation of HIV-1 cores at the nuclear envelope but not specifically at nuclear pores. These observations are consistent with GS-CA1 inhibiting the nuclear translocation of HIV-1 capsid cores through nuclear pores.